2023
DOI: 10.3390/molecules28073078
|View full text |Cite
|
Sign up to set email alerts
|

Esterified Soy Proteins with Enhanced Antibacterial Properties for the Stabilization of Nano-Emulsions under Acidic Conditions

Abstract: Soy protein isolate (SPI), including β-conglycinin (7S) and glycinin (11S), generally have low solubility under weakly acidic conditions due to the pH closed to their isoelectric points (pIs), which has limited their application in acidic emulsions. Changing protein pI through modification by esterification could be a feasible way to solve this problem. This study aimed to obtain stable nano-emulsion with antibacterial properties under weakly acidic conditions by changing the pI of soy protein emulsifiers. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Esterification of soy proteins can elevate their isoelectric point to 8 from 4.5 [80]. Ethanol-esterified soy proteins acquire positive charges in weakly acidic environments, which helps curtail the growth of bacteria with negatively charged cell membranes [81].…”
Section: Esterificationmentioning
confidence: 99%
“…Esterification of soy proteins can elevate their isoelectric point to 8 from 4.5 [80]. Ethanol-esterified soy proteins acquire positive charges in weakly acidic environments, which helps curtail the growth of bacteria with negatively charged cell membranes [81].…”
Section: Esterificationmentioning
confidence: 99%
“…Additionally, the emulsification and foaming properties of these esterified pulse proteins in the acidic pH range of 2.0 to 6.0 surpassed those of the native proteins. Wang et al [52] found that altering the protein isoelectric point (pI) through esterification could be a feasible way to enhance these properties. All esterified-protein nano-emulsion samples exhibited small mean particle sizes, good stability, and an antibacterial-inhibitory effect under weakly acidic conditions (pH 5.0).…”
Section: Chemical Modificationmentioning
confidence: 99%